Implementation Of Community Based Forest Management For Conservation Partners In Conservation Of Dangku Wildlife Sanctuary Forest - Febriyanto Febriyanto; I Made Astra; Cahyadi Setiawan; Martialis Puspito KM (Jurnal Ilmu Sosial Mamangan, 2024)
Forests are the body organ of the earth, where a variety of flora, fauna, mineral resources, and other wealth can be taken from forests that are indispensable to human life. However, the use of forest resources massively destroys forests and consequently alters their functioning. The forest area in Indonesia is 125,797.052 ha with the implementation of deforestation until. December 2021, which is 90.233.159 ha with a total number of decrees of forestation of 2.157 SK. There has been a significant increase in the extent of forestation in the period of the last 10 years to a total of 72% of the total area of Indonesian forest area, while the results of the forest monitoring of Indonesia in 2022 show that the total forested land area of the entire mainland of Indonesia is 96,0 million hectares, or 51.2% of the total land area. From the case that the parties have a chance to misuse or even de-function the land. The situation adds to the author's enthusiasm and interest in identifying any kinds of exploitation and development of Dangku Marga Asylum Forest related to community cohesion, as well as identifying how the implementation of Community Based Forest Management (CBFM) will maintain the sustainability of Dungku Margasatwa Forest. The research was carried out in the area of the Dangku Wildlife Asylum Forest in the Keluang district in Dawas Village, the Tungkal Jaya district, and Tungkal District in Sido Mulyo Village. The study was conducted using a qualitative descriptive approach to describe the conditions to be observed in the field in a more specific, transparent, and in-depth manner. The results of the study indicated that the implementation of community-based forest management in the Dangku Wildlife Refuge Area was categorised as “fairly effective” by identifying some unoptimal assessment indicators.